Digital Innovation in Accounting Systems: Evidence from Emerging Market Enterprises in South Africa - Johan Ferreira (PT. BATARI EDU CALYA, 2024)
This study investigates the impact of digital innovation on accounting information systems (AIS) within emerging market enterprises, with particular focus on South Africa. As digital transformation reshapes business operations globally, understanding how enterprises in emerging markets adopt and benefit from digitalized accounting systems becomes increasingly critical for sustainable economic development. Drawing upon the Technology Acceptance Model (TAM) and structural equation modeling approaches, this research synthesizes evidence from multiple studies examining the relationship between digital technology adoption, AIS quality, and organizational performance. The findings reveal that digital accounting systems significantly enhance operational efficiency, financial performance, and competitive advantage among small and medium enterprises (SMEs). Furthermore, the study identifies key antecedents influencing AIS adoption, including perceived usefulness, perceived ease of use, and technological compatibility. The implications extend to policymakers and practitioners seeking to promote digital transformation in emerging market contexts, particularly within the African continent where Software as a Service (SaaS) and cloud computing present transformative opportunities for enterprise development.